Impact of optimism versus pessimism on life satisfaction in university students - Óscar Gavín-Chocano; Inmaculada García-Martínez; David Molero (Educar, 2023)
Being optimistic or pessimistic is a form of intuitive, premonitory thinking that is conditioned by one’s personal experience. Some authors consider this attitude to be a subjective construction relating to expectations generated, motivation and effort. Others authors consider it to be a personality trait linked to life satisfaction and adaptive response to context. For this study, 561 university students participated, with an average age of 20.31 years (±3.46). The instruments used were the Life Orientation Test (LOT-R) and the Satisfaction with Life Scale (SWLS). The aim of the study was to determine the structure of the LOT-R instrument, since many studies have questioned its unidimensional or twodimensional structure, which compromises the instrument’s validity. Subsequently, it was related to the SWLS through a Structural Equation Model. The results showed that the two-dimensional model (optimism and pessimism) was the most appropriate (χ²/df = 4.36; RMSEA=.072; SRMR=.044; GFI=.960; CFI=.979). Subsequently, the results described above were related to the Life Satisfaction variable, which reinforced the theoretical model proposed. Findings corroborated the double dimensionality of the LOT-R instrument, with a positive relationship between optimism and life satisfaction, and a negative relationship between pessimism and life satisfaction.